2020
DOI: 10.1084/jem.20192386
|View full text |Cite|
|
Sign up to set email alerts
|

Transcription cofactor GRIP1 differentially affects myeloid cell–driven neuroinflammation and response to IFN-β therapy

Abstract: Macrophages (MФ) and microglia (MG) are critical in the pathogenesis of multiple sclerosis (MS) and its mouse model, experimental autoimmune encephalomyelitis (EAE). Glucocorticoids (GCs) and interferon β (IFN-β) are frontline treatments for MS, and disrupting each pathway in mice aggravates EAE. Glucocorticoid receptor–interacting protein 1 (GRIP1) facilitates both GR and type I IFN transcriptional actions; hence, we evaluated the role of GRIP1 in neuroinflammation. Surprisingly, myeloid cell–specific loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 118 publications
(154 reference statements)
0
11
1
Order By: Relevance
“…We can understand the importance of cell clustering through the following example. When we analyzed another data (Table S2 of Mimouna et al) [33], both the reported and our results were not ideal. Analyzing the reasons, we nd that their data clustering methods are different from the other literatures mentioned above.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…We can understand the importance of cell clustering through the following example. When we analyzed another data (Table S2 of Mimouna et al) [33], both the reported and our results were not ideal. Analyzing the reasons, we nd that their data clustering methods are different from the other literatures mentioned above.…”
Section: Discussioncontrasting
confidence: 64%
“…Of course, our cell identi cation process was not smooth sailing. When we analyzed another data (Table S2 of Mimouna et al) [33], we encounter thorny problems. In this report, Louvain graph-based community clustering was used to divide the cells into different clusters, and PanglaoDB was used to identify putative cell and/or activation state for each individual Louvain cluster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this observation, stimulation of SRC-3 with a small molecule stimulator MCB-613 ( 85 ) brings about enrichment of anti-inflammatory MΦs to promote the establishment and maintenance of a pro-reparative environment post myocardial infarction (MI) ( 86 ) ( Figure 2B ). Surprisingly, as opposed to its anti-inflammatory role in peripheral MΦs, SRC-2 drives neuroinflammation through activation of a proinflammatory program in microglia (MG) ( 87 ); conditional KO (cKO) of SRC-2 in myeloid cells significantly reduces experimental autoimmune encephalomyelitis (EAE) severity, which in part is associated with persistence of a homeostatic MG signature, rather than a pro-inflammatory profile and activity that are associated with SRC-2 deficiency in BM and WAT-resident MΦs ( Figure 2A ). This unexpected role of SRC-2 as a driving force of neuroinflammation indicates the functional versatility associated with this NCoA in different MΦ subtypes which is dependent on the environmental conditions and biological context.…”
Section: Coactivators and The Immune Systemmentioning
confidence: 99%
“…Increasingly, it is demonstrated that in the presence of neuroin ammation, the production of IFN-β plays a neuroprotective role in many central neurological diseases, such as Multiple Sclerosis (MS) and Experimental Autoimmune Encephalomyelitis (EAE) [6][7][8]. IFN-β is used clinically as one of the drugs to alleviate the neuroin ammatory response in MS [9]. It can also reduce microglial responsiveness, microglial proliferation and neuroin ammation [10].…”
Section: Introductionmentioning
confidence: 99%